2009
DOI: 10.1016/j.electstud.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Candidate effects and spill-over in mixed systems: Evidence from New Zealand

Abstract: Although mixed member proportional (MMP) systems offer several advantages they also have one potential problem that threatens the legitimacy of electoral outcomes. Some suggest that these systems suffer from a "contamination effect" where candidates have the potential to influence the party list vote which ultimately determines the partisan composition of parliament. This paper examines this theory in New Zealand which has conducted four elections under MMP.The analysis is based on district level data merged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
0
14
0
4
Order By: Relevance
“…Such spillover effects can operate in two directions. Contamination can occur from the proportional representation tier to the majoritarian tier and vice versa (Hainmüller and Kern, 2008;Karp, 2009).…”
Section: Top-down and Bottom-up Electoral Spilloversmentioning
confidence: 99%
“…Such spillover effects can operate in two directions. Contamination can occur from the proportional representation tier to the majoritarian tier and vice versa (Hainmüller and Kern, 2008;Karp, 2009).…”
Section: Top-down and Bottom-up Electoral Spilloversmentioning
confidence: 99%
“…Both models have a long success record and are frequently applied in economics, psychology, consumer research, and related fields, including the domains of travel behavior (e.g., Adamowicz, Louviere, & Williams, 1994;Hensher, 1994;Train, 1978;Wardman, 1988), environmental behavior (e.g., Hanley, Wright, & Adamowicz, 1998;Roberts, Boyer, & Lusk, 2008), political choice behavior (e.g., Bowler, Karp, & Donovan, 2010;Karp, 2009;Nownes, 1992), consumer choices (e.g., Green & Srinivasan, 1978, 1990, or food choices (e.g., Gil & Sánchez, 1997;Loureiro & Umberger, 2005, 2007. For example, using probit models, Ryan and Farrar (2000) analyzed preferences in health care (e.g., treatment in a local clinic vs. treatment in a hospital), and Phillips, Maddala, and Johnson (2002) measured preferences for different HIV tests.…”
mentioning
confidence: 99%
“…Although theoretically providing accountability for local government, running such elections separately nevertheless has a cost for volunteer local party organizations both in time and effort. Indeed, this article suggests that 'contamination' effects are not just evident in electoral outcomes as previous research has indicated (Crisp, 2007(Crisp, : 1468Hainmueller and Kern, 2008;Karp, 2009;Samuels, 2000;Zittel and Gschwend, 2008), they also appear evident in local party campaign efforts; strong campaigns at one level are positively related to strong party campaigns at the other level. This suggests that there may be economies of scale for parties in fighting concurrent elections.…”
Section: Resultsmentioning
confidence: 61%